Utilizing Google Doc to Promote Students Teamwork in Finishing the Assignment - Rabiah; Wahab Syakirul Alim; Achmad Baidawi (ELITE JOURNAL, 2023)
ABSTRACTThis research aims to reveal how google doc facilitates the students in finishing their final project assignment namely making english paper and the advantages of using google doc in teaching and learning process. The approach of this research is qualitative in case study design. The research took place in IAIN Madura, especially the fifth semester of the English Teaching and Learning Program. 26 participants were selected to be part of this research. To achieve the research goal two instruments were used, they are observation and interview. The research findings describe that google doc not only promotes the students to work in a team but also simplify the students in finishing their task efficiently. Keywords: google doc, team work, assignment